Therapeutic options for the treatment of post-acute sequelae of COVID-19: a scoping review - Yu Bin Seo; Yu Jung Choi; Jun-Won Seo; Eun Jung Kim; Jacob Lee; Joon Young Song (BMC Infectious Diseases)
Abstract Objectives This scoping review aimed to summarize the available studies to address the question of which therapeutic agents can be utilized for patients with post-acute sequelae of COVID-19 (PASC). Methods We conducted a systematic search in medical databases, including PubMed and Embase, for studies aligned with our objectives published between January 1, 2020, and July 22, 2024. For each study, we summarized the main symptoms targeted, study design, therapeutic regimens, evaluation tools, and clinical outcomes. Results A total of 413 studies were identified, and 39 studies were included in this review based on relevance to the research objectives. We primarily focused on high-level evidence studies, such as meta-analyses and randomized controlled trials, but observational studies were included when evidence was scarce. Therapeutic agents evaluated included hyperbaric oxygen, ivermectin, metformin, naltrexone, micronutrient supplements, antifibrotic agents, antiviral agents, and selective serotonin reuptake inhibitors (SSRIs). Among these, hyperbaric oxygen, antifibrotic agents, antiviral agents, and SSRIs demonstrated promising results. However, the heterogeneity of PASC symptoms posed challenges in synthesizing findings for specific symptom-based outcomes. Conclusion Given the heterogeneity of symptoms, this review highlights the need for standardized and targeted research to better address the diverse therapeutic needs of patients with PASC. Clinical Trial Not applicable.